PERANAN PREPOPULATED DATA DALAM MENINGKATKAN KEMUDAHAN PELAPORAN PAJAK PERTAMBAHAN NILAI PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA MAKASSAR UTARA - faidul Adziem; Akhmad Akhmad; Mahmud Nuhung; Miftahul Jannah (Jurnal Riset Perpajakan: Amnesty, 2021)
This study aims to determine how the role of Prepopulated Data in increasing the ease of reporting Value Added Tax at the North Makassar Tax Service Office. The research method used is descriptive and tends to use analysis with a qualitative approach to describe how much superiority there is before the prepopulated data and after the prepopulated data. The results of this study indicate that with the new E-invoice feature 3.0, it helps taxpayers to comply and reduce the risk of errors in reporting Value Added Tax. With the 3.0 feature, it is very easy for taxpayers to report their taxes.